ENGINEERING CALCULATION OF EFFICIENCY OF COMBINED LIGHTING SYSTEMS WITH AUTOMATIC CONTROL - A. I. Kirilenko; A. A. Stovpak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
It is proposed to characterize power efficiency of combined lighting systems with automatic control by a coefficient that is specifically determined. Conclusion about the expediency of application of the lighting devices with various luminous intensity curves in the lines parallel to light openings has been made on the basis of the calculations. In order to improve efficiency of such lighting systems it is recommended to have a unified approach to development of artificial and daylight illumination sub-systems and automatic control lighting systems.